Westonci.ca is the premier destination for reliable answers to your questions, provided by a community of experts. Discover precise answers to your questions from a wide range of experts on our user-friendly Q&A platform. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.
Sagot :
Let's analyze the functions [tex]\( f(x) = 3x^3 + 2 \)[/tex] and [tex]\( g(x) = \sqrt[3]{\frac{x-2}{3}} \)[/tex] to determine whether any of the statements I, II, or III are true.
1. First, we need to check if [tex]\( f(g(x)) = x \)[/tex] for all real [tex]\( x \)[/tex].
[tex]\[ f(g(x)) = f\left(\sqrt[3]{\frac{x-2}{3}}\right) \][/tex]
Now, let's substitute [tex]\( g(x) \)[/tex] into [tex]\( f(x) \)[/tex]:
[tex]\[ f\left(\sqrt[3]{\frac{x-2}{3}}\right) = 3\left(\sqrt[3]{\frac{x-2}{3}}\right)^3 + 2 \][/tex]
Simplifying inside the brackets:
[tex]\[ 3 \left(\frac{x-2}{3}\right) + 2 = x - 2 + 2 = x \][/tex]
Therefore, [tex]\( f(g(x)) = x \)[/tex] is true.
2. Next, let's verify if [tex]\( g(f(x)) = x \)[/tex] for all real [tex]\( x \)[/tex].
[tex]\[ g(f(x)) = g(3x^3 + 2) \][/tex]
Now, substitute [tex]\( f(x) \)[/tex] into [tex]\( g(x) \)[/tex]:
[tex]\[ g(3x^3 + 2) = \sqrt[3]{\frac{3x^3 + 2 - 2}{3}} = \sqrt[3]{x^3} = x \][/tex]
Therefore, [tex]\( g(f(x)) = x \)[/tex] is also true.
3. Finally, we check if the functions [tex]\( f \)[/tex] and [tex]\( g \)[/tex] are inverse functions. For this, both [tex]\( f(g(x)) = x \)[/tex] and [tex]\( g(f(x)) = x \)[/tex] must hold true.
Since we have shown that both [tex]\( f(g(x)) = x \)[/tex] and [tex]\( g(f(x)) = x \)[/tex] for all [tex]\( x \)[/tex], [tex]\( f \)[/tex] and [tex]\( g \)[/tex] are indeed inverse functions.
Given these findings:
- I: [tex]\( f(g(x)) = x \)[/tex] is true for all real [tex]\( x \)[/tex].
- II: [tex]\( g(f(x)) = x \)[/tex] is true for all real [tex]\( x \)[/tex].
- III: Functions [tex]\( f \)[/tex] and [tex]\( g \)[/tex] are inverse functions.
Thus, the correct answer is:
C. I, II, and III are true.
1. First, we need to check if [tex]\( f(g(x)) = x \)[/tex] for all real [tex]\( x \)[/tex].
[tex]\[ f(g(x)) = f\left(\sqrt[3]{\frac{x-2}{3}}\right) \][/tex]
Now, let's substitute [tex]\( g(x) \)[/tex] into [tex]\( f(x) \)[/tex]:
[tex]\[ f\left(\sqrt[3]{\frac{x-2}{3}}\right) = 3\left(\sqrt[3]{\frac{x-2}{3}}\right)^3 + 2 \][/tex]
Simplifying inside the brackets:
[tex]\[ 3 \left(\frac{x-2}{3}\right) + 2 = x - 2 + 2 = x \][/tex]
Therefore, [tex]\( f(g(x)) = x \)[/tex] is true.
2. Next, let's verify if [tex]\( g(f(x)) = x \)[/tex] for all real [tex]\( x \)[/tex].
[tex]\[ g(f(x)) = g(3x^3 + 2) \][/tex]
Now, substitute [tex]\( f(x) \)[/tex] into [tex]\( g(x) \)[/tex]:
[tex]\[ g(3x^3 + 2) = \sqrt[3]{\frac{3x^3 + 2 - 2}{3}} = \sqrt[3]{x^3} = x \][/tex]
Therefore, [tex]\( g(f(x)) = x \)[/tex] is also true.
3. Finally, we check if the functions [tex]\( f \)[/tex] and [tex]\( g \)[/tex] are inverse functions. For this, both [tex]\( f(g(x)) = x \)[/tex] and [tex]\( g(f(x)) = x \)[/tex] must hold true.
Since we have shown that both [tex]\( f(g(x)) = x \)[/tex] and [tex]\( g(f(x)) = x \)[/tex] for all [tex]\( x \)[/tex], [tex]\( f \)[/tex] and [tex]\( g \)[/tex] are indeed inverse functions.
Given these findings:
- I: [tex]\( f(g(x)) = x \)[/tex] is true for all real [tex]\( x \)[/tex].
- II: [tex]\( g(f(x)) = x \)[/tex] is true for all real [tex]\( x \)[/tex].
- III: Functions [tex]\( f \)[/tex] and [tex]\( g \)[/tex] are inverse functions.
Thus, the correct answer is:
C. I, II, and III are true.
We appreciate your time on our site. Don't hesitate to return whenever you have more questions or need further clarification. Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. Your questions are important to us at Westonci.ca. Visit again for expert answers and reliable information.